2017
DOI: 10.1080/87565641.2017.1306528
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Orientation and Navigation in Children With Perinatal Stroke

Abstract: As a focal injury in an otherwise healthy child, perinatal stroke provides a clinical model of developmental brain plasticity. In this study, we report evidence that children with perinatal periventricular venous infarcts perform as well as control children on a video game that tests navigation abilities. In addition, children with a history of perinatal arterial strokes overcame initial deficits in navigation performance after additional practice. These findings lend support to the hypothesis that a complex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The Digit span WISC-IV subtests-forward and backward- served as a control verbal measure of spatial memory. Parents and children filled out a pilot questionnaire on everyday visuo-spatial and navigation abilities (Santa Barbara Sense of Direction Scale-Parent and Child Version: p-CBSOD and c-CBSOD) adapted by Murias et al ( 45 ) (see Supplementary Material 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Digit span WISC-IV subtests-forward and backward- served as a control verbal measure of spatial memory. Parents and children filled out a pilot questionnaire on everyday visuo-spatial and navigation abilities (Santa Barbara Sense of Direction Scale-Parent and Child Version: p-CBSOD and c-CBSOD) adapted by Murias et al ( 45 ) (see Supplementary Material 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…There is considerable research on both domains with TD children (for reviews see Newcombe et al, ; Newcombe & Frick, ; Vasilyeva & Lourenco, ). Very few studies have examined the effects of early brain injury on the development of intrinsic and extrinsic spatial representations (e.g., Murias et al, ; Stiles et al, ). Spatial skills of children with PL have mostly been investigated regarding the visuospatial skills and spatial grouping (e.g., Askhoomoff, Feroleto, Doyle, & Stiles, ; Schatz, Ballantyne, & Trauner, ; Stiles, ; Stiles, Stern, Trauner, & Nass, ).…”
Section: Specific Skills Related To Stem: Spatial and Mathematical Skmentioning
confidence: 99%
“…Extrinsic skills like spatial navigation have not been studied extensively in this population. One recent study by Murias et al (2017) showed that children with PL perform similarly to TD children on a video game that tests their spatial navigational abilities. They conclude that cognitive skills that rely on distributed networks can be less vulnerable to early injury and can be more resilient (Kolb, Mychasiuk, Williams, & Gibb, 2011).…”
Section: Spatial Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing allocentric and egocentric frames of reference separately is particularly relevant not only with the objective of understanding their development and average functioning, but also to use it as a tool to evaluate different populations with pathologies. In children, certain clinical populations such as spinal muscular atrophy (Rivière & Lécuyer, 2002) or perinatal stroke (Murias et al, 2017) show an adequate spatial memory for their developmental stage. Nevertheless, difficulties in both egocentric and allocentric frameworks have been found in developmental topographical disorientation (Iaria & Barton, 2010) and in Williams syndrome (Bernardino, Mouga, Castelo‐Branco, & Van Asselen, 2013; Broadbent, Farran, & Tolmie, 2014), while in Down syndrome (Lavenex et al, 2015), in cerebral palsy (Belmonti, Fiori, Guzzetta, Cioni, & Berthoz, 2015), in fetal alcohol syndrome (Hamilton, Kodituwakku, Sutherland, & Savage, 2003) and in children born prematurely (Fernandez‐Baizan, Alcantara‐Canabal, Solis, & Mendez, 2020) a worse allocentric‐based orientation is found, which, as we have already commented, has been the most studied.…”
Section: Introductionmentioning
confidence: 99%